Estudo sobre a qualidade do ensino de uma escola de nível médio localizada em Vitória, ES - Trancoso, Emily Moreira (2022)
This article sought to measure the quality of teaching in a secondary school through the servqual tool developed by Parasuraman, Zeithaml and Berry, which makes it possibleto identify whether the customer's expectation is aligned with the service performed. Thus, it is possible to analyze points that have flaws, in order to improve the quality and reputation of teaching, also seeking the school's competitiveness in the field. The research was quantitative and the results were obtained through the responses of students through an online questionnaire, consisting of assessments in various spheres that make up the service provided and based on the expectations of students. As a result of the students' assessment, it was possible to observe items where the service offered was far from the service performed, in others where the perception was close to or above expectations. Therefore, it is possible to understand the relevance of the Servqual tool, which allows us a very broad view of essential points for improvement, consequently, of the advancement of the service provided.